Maghemite nanoparticle‐decorated hollow fiber electromembrane extraction combined with dispersive liquid–liquid microextraction for determination of thymol from Carum copticum. (2nd August 2016) - Khajeh, Mostafa; Pedersen‐Bjergaard, Stig; Bohlooli, Mousa; Barkhordar, Afsaneh; Ghaffari‐Moghaddam, Mansour
Abstract: BACKGROUND: A novel technique using maghemite nanoparticle‐decorated hollow fibers to assist electromembrane extraction is proposed. Electromembrane extraction combined with dispersive liquid–liquid microextraction (EME‐DLLME) was applied for the extraction of thymol from Carum copticum, followed by gas chromatography with flame ionization detection (GC‐FID). RESULTS: The use of maghemite nanoparticle‐decorated hollow fibers was found to improve the extraction efficiency of thymol significantly. Important operational parameters, including pH of acceptor phase, extraction time, voltage and temperature, were investigated and optimized. At the optimal conditions, linearity in the range 4–1800 µg L −1 with a determination coefficient of 0.9996 was obtained. The limit of detection was 0.11 µg L −1 (S/N = 3) and the pre‐concentration factor was 200. The intra‐ and inter‐day precision was 5.9 and 2.2% respectively. The intra‐ and inter‐day accuracy was higher than 93.6%. CONCLUSION: The results indicated that EME‐DLLME/GC‐FID is a useful technique for the extraction and determination of thymol in C copticum . © 2016 Society of Chemical Industry